Use of Coffee, Caffeinated Drinks and Caffeine Tablets for Cognitive Enhancement in Pupils and Students in Germany - Franke, A. G.; Christmann, M.; Bonertz, C.; Fellgiebel, A.; Huss, M.; Lieb, K. (Pharmacopsychiatry, 2011)
Substance use for cognitive enhancement (CE) is a topic of increasing importance. There are only few data about substances, prevalence rates and factors associated with CE. The aim of this study was to assess first data about the use of coffee, caffeinated drinks and caffeine tablets for CE at school and university.A self-report questionnaire was developed to analyze 1 547 pupils and students about their use of coffee, caffeine tablets, and caffeinated drinks for CE and factors associated with this use.Lifetime, past-year, and past-month prevalence for the use of coffee for CE was 53.2%, 8.5%, and 6.3%, for the use of caffeinated drinks 39%, 10.7%, and 6.3%, and for the use of caffeine tablets 10.5%, 3.8%, and 0.8%. Use of caffeinated substances for CE was influenced by gender and school grades.The use of coffee and caffeinated drinks for CE was found to be widespread in the surveyed population. Although the use of caffeine tablets was found to be smaller than the above-mentioned means, it still indicates a relatively high disposition for using tablets for purposes of CE.
Keywords: cognitive enhancement; caffeine; coffee; caffeinated drink(s); caffeine tablets